Influencing factors and mechanisms of blistering in epoxy asphalt mixtures for steel deck pavements. (17th January 2022) - Liao, Menghui; Luo, Rong
Highlights: Blister test can effectively simulate the occurrence of blister disease. Temperature has the greatest influence on the blister growth. Blister disease cannot recover to the initial state after completing a cycle. Abstract: The epoxy asphalt mixture applied on a steel bridge deck usually experiences blisters in summer construction, which seriously shortens the service life of the pavement structure. In order to reduce the frequency of blisters and improve the construction quality, three main influencing factors of blistering (environment temperature, curing time of epoxy asphalt mixture, and initial debonding area) and the deformation characteristics and growth mechanisms of blistering were investigated. A simulation test of pavement blistering was first designed, and the test parameters were obtained by analyzing the thermodynamic process of droplet evaporation; then, the displacement sensor was used to measure the growth of blistering, and finally the influence of the three main factors on blistering for pavements was analyzed. The main conclusions are as follows: (a) temperature has the greatest influence on the blistering growth, while the initial debonding area has the least influence on the blistering growth; (b) blistering growth in a pavement layer reaches its limit within 30 to 90 min during the curing period; (c) the deformation of blistering is a rapid process if the ambient temperature exceeds 30℃; and (d) the ability of epoxy asphalt mixtures to resist deformation positively correlates with curing time. It is hard to observe blistering at low temperature (30℃) if the epoxy asphalt mixture was paved for more than 48 h. Finally, effective measures would be proposed for improvement from three dimensions are respectively prevention, detection time, and detection method.